Construction and Computation of the College English Teaching Path in the Artificial Intelligence Teaching Environment - Liu, Shaojie (Computational intelligence and neuroscience, 2022)
Today, English is the world’s main international language and is widely spoken. In this context, the learning of English has long been valued by all countries. In addition, English plays an essential role in the process of economic globalization, specifically in the majority of countries where English is not the native language. At the same time, as China’s integration into the world grows, the importance of English has become more pronounced, and the demand for English language skills has increased. At present, China’s ever-expanding opening to the outside world, its developing science and technology, and its rising international status have created an urgent need for English-speaking professionals. This will lay the foundation for China’s economic and social development and enable China to play a greater and more active role in international affairs, which has great practical and far-reaching historical significance. At present, the traditional English teaching mode has been criticized due to a great number of issues. At the same time, the new English language standards and the change of evaluation methods have created new demands on English teaching methods. As a result, with the development of artificial intelligence technology, the application of artificial intelligence technology in the field of education has brought new directions for the optimization of English classroom. In addition, diversified network technologies also provide new support for the realization of intelligent and collaborative English classroom teaching. To be specific, the maturity of English intelligent speech synthesis and intelligent speech evaluation technologies has enabled intelligent technologies to reach or even surpass the level of human teachers in certain areas. However, due to the limitations of the market environment and evaluation methods, the products that can focus on English classroom teaching are not highly intelligent and less collaborative. What is more, the process of English classroom intelligence has stagnated compared to other subjects. Obviously, from the perspective of integrating artificial intelligence technology with English classroom, it is quite necessary and feasible to design and develop an intelligent teaching assistant that can be applied to college English teaching. As information technology continues to evolve, both national and teacher levels are beginning to focus on how it can be better used in the teaching of subjects. Therefore, the use of online information technology in teaching and learning presents a great opportunity for research and practice in English language learning at the university level.